Endocrinology of thermoregulation in birds in a changing climate - Ruuskanen Suvi; Hsu Bin-Yan; Nord Andreas (ELSEVIER IRELAND LTD, 2022)
The ability to maintain a (relatively) stable body temperature in a wide range of thermal environments by use of endogenous heat production is a unique feature of endotherms such as birds. Endothermy is acquired and regulated via various endocrine and molecular pathways, and ultimately allows wide aerial, aquatic, and terrestrial distribution in variable environments. However, due to our changing climate, birds are faced with potential new challenges for thermoregulation, such as more frequent extreme weather events, lower predictability of climate, and increasing mean temperature. We provide an overview on thermoregulation in birds and its endocrine and molecular mechanisms, pinpointing gaps in current knowledge and recent developments, focusing especially on non-model species to understand the generality of, and variation in, mechanisms. We highlight plasticity of thermoregulation and underlying endocrine regulation, because thorough understanding of plasticity is key to predicting responses to changing environmental conditions. To this end, we discuss how changing climate is likely to affect avian thermoregulation and associated endocrine traits, and how the interplay between these physiological processes may play a role in facilitating or constraining adaptation to a changing climate. We conclude that while the general patterns of endocrine regulation of thermogenesis are quite well understood, at least in poultry, the molecular and endocrine mechanisms that regulate, e.g. mitochondrial function and plasticity of thermoregulation over different time scales (from transgenerational to daily variation), need to be unveiled. Plasticity may ameliorate climate change effects on thermoregulation to some extent, but the increased frequency of extreme weather events, and associated changes in resource availability, may be beyond the scope and/or speed for plastic responses. This could lead to selection for more tolerant phenotypes, if the underlying physiological traits harbour genetic and individual variation for selection to act on - a key question for future research.